Pelaksanaan Proses Produksi pada Usaha Kecil Batik Pringgokusumo Banyuwangi (Implementation of Production Process on Pringgokusumo Batik Small Business in Banyuwangi) - Wangi, Rima Rahma; Poernomo, Djoko; S, Suhartono (e-Sospol, 2019)
AbstractBatik industry is a very potential industry to be developed. In batik industry, stamp batik production gives a positive contribution. Apart from the economic side, it is undeniable that the existence of stamp batik production is getting bigger. Many new batik industries grow in Banyuwangi. Therefore, this condition has encouraged Pringgokusumo Batik Small Business to maintain the existence of its batik company to survive and develop by increasing its production, especially in the implementation of stamp batik production process. Moreover, the consumers increasingly demand the stamp batik products. This descriptive research employed a qualitative approach which aims to describe the Implementation of Production Process in Pringgokusumo Batik Small Business. Key informant in this research was determined purposively. Research data were collected through observation, interview, and documentation. Then, the data were analyzed by using domain and taxonomy analyses. To test data validity, researchers used triangulation of source, technique, and time; so that, the data obtained were valid. The findings indicated that Pringgokusumo Batik Small Business has been able to minimize the number of defective batik products that occurred due to irrelevance on each stage of the production process. The production of stamp batik every year was still stable, even though the target of production every year was still not achieved. One of them was due to the limited availability of labors in the stamp batik department.Keywords: Production process, Stamp Batik